CTNI-59. A MULTICENTER OBSERVATIONAL STUDY OF CS-131 SEEDS EMBEDDED IN A COLLAGEN CARRIER TILE FOR NEWLY DIAGNOSED AND RECURRENT OPERABLE INTRACRANIAL NEOPLASMS – TRIAL IN PROGRESS. (12th November 2021) - Dunbar, Erin; McCracken, David; nowlan, adam; Chen, Clark; Dusenbery, Kathryn; Ferreira, Clara; Kotecha, Rupesh; McDermott, Michael; Jaikumar, Sivakumar; Shen, Colette; Monyak, David; Trusheim, John; et al.
Abstract: BACKGROUND: For patients with operable intracranial neoplasms, there are opportunities to augment local control beyond traditional methods, such as external beam radiation therapy. Brachytherapy, the implantation of radioactive sources into the resection cavity, can be useful in this setting by providing immediate initiation of radiation and limiting the exposure of surrounding normal tissue to radiation. Traditional intracranial brachytherapy has been limited by uneven dose distributions, complicated workflows, extended procedural times, cost of dedicated equipment, and frequent adverse events. To address these issues, a permanently implanted device with Cs-131 radiation seeds embedded in a bioresorbable collagen carrier tile (GammaTile, GT Medical Technologies, Tempe, AZ USA) was developed. Described as surgically targeted radiation therapy (STaRT), it is FDA-cleared for use in newly-diagnosed malignant intracranial neoplasms and recurrent intracranial tumors, and has demonstrated excellent safety and efficacy in early commercial use. The primary objectives of this multicenter, prospective, observational (phase IV) registry study are to evaluate "real-world" clinical outcomes and patient-reported outcomes that measure the safety and efficacy of STaRT using the GammaTile. METHODS: Patients undergoing resection (R) of brain tumors with intra-operative GammaTile placement are eligible for enrollment. Planned sample size is 600 at up to 50 enrolling sites. First subject was enrolled 10/14/2020. Tumor pathology, overall survival, radiation- and surgery-related adverse events, patient- and provider-reported quality of life, serial MRIs, and timing of surgical bed and/or distant recurrence are collected. Powered primary endpoints for recurrent brain metastases, recurrent glioblastoma, and recurrent meningioma (surgical bed-progression free survival (PFS), overall survival, and PFS, respectively), compare STaRT to standard-of-care benchmarks. Results will be used to improve awareness and access to this treatment, benchmark clinical outcomes in the real-world setting, allow for comparisons to existing treatments, facilitate the design of future clinical trials, and contribute to the optimal sequencing of treatments for intracranial neoplasms.